Improving the Quality of Islamic Boarding School Education through Organizational Commitment of Human Resources - Jafar Syahbuddin Ritonga (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Improving the quality of Islamic boarding school education is essential to meet the demands of modern times and global competition. These institutions are expected not only to produce academically capable students but also those with strong character, noble morals, and spirituality. A key factor influencing the quality of Islamic boarding school education is the organizational commitment of human resources, particularly educators and educational staff. This study examines the role of human resource commitment in enhancing the quality of Islamic boarding school education, using a library research method by reviewing books, journals, and previous studies on organizational commitment and education quality. The findings highlight that organizational commitment, expressed through affective, normative, and sustained commitment, significantly impacts education quality. These dimensions encourage educators and staff to work professionally and responsibly, focusing on quality in both learning and management. Additionally, pesantren leadership and an organizational culture rooted in Islamic values further strengthen this commitment, leading to a positive and sustainable impact on education quality. The study concludes that fostering strong organizational commitment is crucial for improving pesantren education, urging managers to prioritize human resource development through effective management, visionary leadership, and a conducive organizational culture.